2014
DOI: 10.3892/etm.2014.1876
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning improvement effects of ulinastatin on brain injury following cardiopulmonary resuscitation

Abstract: The aim of the present study was to determine the effects of ulinastatin (UTI) on brain injury in rats subjected to cardiopulmonary resuscitation (CPR) following asphyxial cardiac arrest (CA) and identify the underlying mechanisms. In total, 100 healthy male Wistar rats were randomly divided into control and treatment groups (n=50). After 4 min of asphyxial CA, all the rats were immediately subjected to CPR. The treatment group animals were administered 15 mg/kg UTI at the onset of resuscitation. The mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Those specific brain regions were selected in our study because expression of PICs and their receptors is upregulated in those regions following CA in rats and in general they are also more related to neurological deficits after cerebral ischemia than other brain regions [18, 20]. Our results showed that CA amplifies the levels of IL-6 and TNF-α in addition to IL-1β, which is consistent with the previous report [11]. Notably, we further found that the protein expression of PIC receptors such as IL-1R, IL-6R and TNFR1 were also increased in the cortex and hippocampus CA1 regions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Those specific brain regions were selected in our study because expression of PICs and their receptors is upregulated in those regions following CA in rats and in general they are also more related to neurological deficits after cerebral ischemia than other brain regions [18, 20]. Our results showed that CA amplifies the levels of IL-6 and TNF-α in addition to IL-1β, which is consistent with the previous report [11]. Notably, we further found that the protein expression of PIC receptors such as IL-1R, IL-6R and TNFR1 were also increased in the cortex and hippocampus CA1 regions.…”
Section: Discussionsupporting
confidence: 90%
“…In an important prior study [11], UTI has been shown to play a protective role in CA induced-cerebral ischemia by attenuating brain edema and inflammatory responses (i.e., central IL-6 and TNF-α) and thereby improving survival and neurological function. In contrast, in the present study, we further studied the effects of UTI on the protein expression levels of PIC receptors in CA rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti‐inflammatory activities, organ protective effect, and clinical effectiveness of ulinastatin in several SIRS conditions have been investigated in many animal studies14, 15, 16 and clinical studies 5, 10, 13, 17, 18, 19. Based on these results, we hypothesized that ulinastatin would have beneficial effects on MOF patients.…”
Section: Discussionmentioning
confidence: 98%
“…Recombinant human activated protein C (APC), an anti-inflammatory agent, benefits severe sepsis patients via rearrangement of actin-phosphomyosin light chain (20). Ulinastatin (UTI), another inhibitor of inflammation, inhibits the production of TNF-␣ and interleukin-6 (IL-6) by suppressing toll-like receptor 4 (TLR4) and the downstream signal pathway (14,28,48,50). Such therapies, including APC and UTI, fail to decrease the morbidity and mortality associated with sepsis, likely because the pathogenesis of sepsis is not completely understood.…”
mentioning
confidence: 99%